The Role Of Integrated Law Enforcement (GAKKUMDU) In Handling Election Crime - Jannah, Raudhatul; Daming, Saharuddin; Lestari, Nisa (Universitas Ibn Khaldun Bogor, 2025)
This research discusses the role of Integrated Law Enforcement (Gakkumdu) in handling election crimes, which often experience obstacles due to weak inter-agency coordination, lack of quality human resources, and budget limitations. This research aims to identify inhibiting factors and offer effective solutions to increase the effectiveness of integrated law enforcement in elections. The method used is a qualitative approach by collecting data through interviews and document study, which is then analyzed in depth. The research results show that improving the quality of human resources through continuous training, simplifying operational procedures, and increasing transparency and public participation are strategic steps that need to be taken. Therefore, this research suggests increasing inter-agency coordination, adequate budget allocation, and strengthening regulations as an effort to overcome obstacles to integrated law enforcement.